PENGARUH BEASISWA TERHADAP MOTIVASI BELAJAR MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS SRIWIJAYA - Raka Ramadhon; Riswan Jaenudin; Siti Fatimah (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2017)
This research aimed to prove the influence of scholarship on learning motivation. This research used the quantitative descriptive method. Subjects in this research were students of Economics Education Sriwijaya University Indralaya Campus from batch 2013 to 2016. Where students who received scholarships amounted to 47 students, and who did not receive scholarships amounted to 63 students. Data collection techniques used questionnaires and documentation. Data Analysis techniques used percentage formula then learning motivation of students who received scholarships is compared to students who did not receive scholarships to look for the influence of scholarship on learning motivation. The results showed the learning motivation if seen from the average questionnaire score of each respondent, students who received scholarships amounted to 78.79. While the learning motivation of students who did not receive scholarship amounted to 75.05. The result of learning motivation analysis if seen from the indicator, the students who received scholarship amounted 78,43%. While the students who did not receive scholarships amounted to 73.75%. Based on the conclusions that had been obtained, it could be suggested for government and private institutions in order to provide scholarships to students to support student learning motivation. For students who received a scholarship must maintain the learning motivation that already high category because it could be useful for learning activities to obtain good results.